(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objectives: Dehydrocostus lactone (DDL) natural product of Eerdun Wurile that has been reported to have anti-inflammatory, anticancer, and anti-proliferation effect. However, no research has been done regarding mechanism of DDL on microglial cells in the brain. Moreover, Schlafen (Slfn) genes are considered to play important regulatory roles for normal cell growth and differentiation of the immune and hematopoietic systems. Among schlafen genes, Slfn-4 is much modulated during macrophage stimulation and differentiation and implicates macrophage in responses to pathogens. The present study was conducted to investigate effects of DDL on Slfn-4 gene expression in lipopolysaccharide (LPS)-stimulated microglial cells. Methods: The anti-inflammatory effects of DDL were studied using LPS-stimulated murine BV2 microglia. BV2 were cultured in DMEM then 4pM DDL were added. Then BV2 was treated with 1 ng/ml LPS for 24 hours to stimulate. Results: LPS alone increased Slfn-4 mRNA expression in BV2 microglial cells (p < 0.01). In contrast, DDL pre-treatment significantly inhibited LPS-induced Slfn-4 mRNA expression (p < 0.05). Conclusions: DDL inhibits the expression of Slfn-4 gene transcripts related with inflammation, activated by LPS in the microglia cells.